Using Microcomputers in Teaching Vocational Agriculture - American Vocational Association, Alexandria, VA.; Barrick, R. Kirby; American Vocational Association, Alexandria, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
This collection of articles is designed to help vocational agriculture teachers use microcomputers in teaching. The guide covers both the different types of software and the ways they can be applied in teaching. The guide is organized in three sections. The first section covers types of programs and includes "Selection of Microcomputer Hardware and Software for Agricultural Education" (Camp); "Electronic Spreadsheet Applications" (Stitt et al.); "Data Bases for Vocational Agriculture" (Moeller); "Text Editing and Word Processing" (Malpiedi); and "Using Agricultural Information and Networking Services" (Miller, Gamble). The second section provides practical tips on incorporating the computer into an instructional program, including "Computer-Assisted Instruction in Vocational Agriculture" (Foster); "Microcomputers in Supervised Occupational Experience Programs" (Briers); and "Using Microcomputers with the Future Farmers of America" (Carter, Chizek). The final section suggests sources of help for "Generating Instructional Materials" (Giesemann) and "Teaching Students to Use Microcomputers" (Bowen). The articles mention brand names of computer hardware and software and provide comparisons of features as well as prices of the various software programs. (KC)
Availability: Publications Committee, Agricultural Education Division, American Vocational Association, 1410 King Street, Alexandria, VA 22314.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agricultural Education; Computer Assisted Instruction; Computer Managed Instruction; Computer Oriented Programs; Computer Software; Computer Uses in Education; Data Processing; Database Management Systems; Databases; Microcomputers; Postsecondary Education; Program Costs; Secondary Education; Vocational Education; Word Processing; Guides, Classroom -- Teacher